2009
DOI: 10.1177/0893318909351433
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of the Internet by Public Relations Professionals in the Private and Public Sectors of Saudi Arabia

Abstract: Managers from Western cultures tend to assume that efficiency and profitability will drive the adoption of new technologies by multinational conglomerates. The present study shows that for non-Western organizations, the sector that the organization operates in (public or private) and its decision-making style are also relevant factors. The research employs the diffusion of innovation model to explore Internet adoption by public relations professionals in Saudi Arabian organizations. A survey of 354 public rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In addition, professionals who received a greater level of support and encouragement from senior management were more likely to post on Instagram. Public relations professional need a nurturing and supportive work environment, which complements the literature showing level of employee satisfaction increases productivity (Chen, Silverthorne, & Hung, 2006;Tourish & Hargie, 2009), performance (Ruck & Welch, 2012) and adoption of the Internet for public relations tasks (Al-Shohaib et al, 2009).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, professionals who received a greater level of support and encouragement from senior management were more likely to post on Instagram. Public relations professional need a nurturing and supportive work environment, which complements the literature showing level of employee satisfaction increases productivity (Chen, Silverthorne, & Hung, 2006;Tourish & Hargie, 2009), performance (Ruck & Welch, 2012) and adoption of the Internet for public relations tasks (Al-Shohaib et al, 2009).…”
Section: Discussionmentioning
confidence: 70%
“…Ruck and Welch (2012) and Sluss et al (2008) argue organizational support is a key predictor of levels of productivity and performance among employees. Al-Shohaib et al (2009) found that organizational encouragement was a predictor of adoption of the Internet for public relations in Saudi Arabia. Accordingly, it is expected that higher levels of support and encouragement by senior management for public relations and communication practitioners to use social media will predict Instagram posting activities.…”
Section: Senior Management Support and Encouragementmentioning
confidence: 99%
“…Other studies have found that the acceptance of the online PR practice concept is related to authoritarian decision-making and a lack of education and skills (Al-Shohaib, Kandari, & Abdulrahim, 2009;Al-Shohaib, Frederick, Jamal Al-Kandari, & Dorsher, 2010;Ayish, 2005;Bashir & Aldaihani, 2017;James, 2007;Fitch, 2009;Kirat, 2005Kirat, , 2006Kirat, , 2007Kirat, , 2016Robson & James, 2013;Vardeman-Winter & Place, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In such cultures both the managers and the subordinates accept unequal relationships. Decision making style is known to be an important factor influencing technology adoption (Sarosa & Underwood, 2005;Al-Shohaib, Frederick, Al-Kandari & Dorsher, 2010).…”
Section: Decision Making Stylementioning
confidence: 99%